Pollution, Climate change and Strategies to Increase Maize Production - An Overview - Mahajan, Vinay; Singh, KP (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 5 No 4 (2018): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
In past, climatic parameters have seen to undergo changes, especially temperature and rainfall. The global temperature has increased significantly which has directly or indirectly affected economically important crops as well as humans. There has been an overall decrease in rainfall and increased fluctuation in temperature in various parts of the country. Pollutants cause severe injury to economically important plants and have caused biotic and abiotic stresses especially in all crops. Burning of crop residues surrounding especially around metro cities is a major concern. Fast growing peri-urban agriculture and industrialization has been associated with pollution threaten urban food production and its quality. The harvest of crop residues using latest farm machinery that converts them into bales which can be efficiently transported to storage or far-off markets. Sewage water and industrial wastes has been a major concern in peri-urban agriculture and animal husbandry. A multi-prong approach needs to be followed in crops. Development of new climate resilient cultivars/crops beneficial to humans and use of environment friendly technology may help in combating pollution and climate change. How to cite this article: Mahajan V, Singh KP. Pollution, Climate change and Strategies to Increase Maize Production - An Overview. J Adv Res Alt Energ Env Eco 2018; 5(4): 10-14. DOI: https://doi.org/10.24321/2455.3093.201802